دور النظام المحاسبي الأساسي في إعداد حساب الناتج المحلي في القطاع العام الاقتصادي ( دراسة تطبيقية) - الصبَّاغ سامر (Latakia University Journal - Economic and Legal Sciences Series, 2013)
صدر النظام المحاسبي الأساسي بموجب المرسوم التشريعي رقم (490) بتاريخ 26/12/2007 , ليحل محل النظام المحاسبي الموحد الصادر بموجب المرسوم التنظيمي رقم (287) بتاريخ 25/1/1978 , واعتبر نافذ المفعول بدءاً من 1/1/2009 . هدفت هذه الدراسة إلى التعرف على دور النظام المحاسبي الأساسي في إعداد حسابات الإنتاج والناتج المحلي في جهات القطاع العام ذات الطابع الاقتصادي ؛ وذلك بما ينسجم مع متطلبات تطبيق النظام الدولي للحسابات القومية الصادر في عام 1993 . وقد توصلت الدراسة إلى أن مخرجات النظام المحاسبي الأساسي وتحديداً قائمتي الدخل والتشغيل والإنتاج تُقدِّم مدخلات ملائمة لإعداد تلك الحسابات ؛ مما يُمكِّن من الاستغناء عن الاستمارات الإحصائية والنماذج التقديرية المُتبَّعة حالياً . وقد انتهت الدراسة إلى وضع المقترحات الملائمة لتقديم البيانات اللازمة للحسابات القومية . Basic accounting system was released under the Legislative Decree No. (490) dated 26/12/2007, to replace the unified accounting system issued under the Regulatory Decree No. (287) dated 25/01/1978, and considered effective as of 1/1/2009. This study aimed to identify the role of the basic accounting system in preparing the production and domestic product account in the economic public sector entities of an economic nature ; and it is consistent with the requirements of application of the international system of national accounts issued in 1993. The study found that the output of the basic accounting system, specifically income, operating and production statements, provide appropriate input for the preparation of that accounts ; making it possible to dispense with the estimated forms and statistical models currently followed. The study concluded by developing appropriate proposals to provide the necessary data for the national accounts.